Congenital herpes simplex II (HSV-2) with limb abnormalities. (7th June 2011) - Wynn-Davies, A C; Akuma, A O; Fraser, M
Abstract : Background and aims: The classical presentation of congenital HSV infection is grouped vesicles on an erythematous base and/or widespread skin erosions. Associated limb malformations have been reported only once. Methods: We present a case of congenital HSV-2 infection in a preterm male infant with extensive skin denudation, vesico-pustules and limb abnormality. Results: He was born to non-consanguineous parents at 28 weeks gestation with a hypoplastic left hand without nails, severe skin sloughing over the left side of his body and occasional vesicles. Mother remained asymptomatic throughout pregnancy without any history of illicit drug use or teratogen exposure. He showed hepatosplenomegaly and elevated liver enzymes. Abdominal ultrasound revealed liver and spleen calcifications. Cranial ultrasound scan revealed areas of cerebritis and ischaemia. HSV-2 DNA was detected in skin swabs and blood samples. Cerebrospinal fluid (CSF) was not obtained because of the risk of iatrogenic central nervous system infection. Maternal blood analysis showed evidence of recent HSV-2 infection. He was treated, following infection screening, with high-dose acyclovir, benzylpenicillin, gentamicin and fluconazole. At day 35, his skin was almost healed with residual cicatrisation, absent HSV-2 DNA on repeat swabs; and resolved viraemia. IV acyclovir was discontinued and oral suppressive therapy was commenced. Conclusions: This case demonstrates that congenital HSV 2 infection should be considered in newborn infants presenting with limb hypoplasia and skin lesions.